Problematika Penerapan Pasal 4 Undang-Undang No. 33 Tahun 2014 Tentang Jaminan Produk Halal Di Kota Sukabumi - Jasmine Syifa Azzahra Susilo; Asti Sri Mulyanti; Temmy Fitriah Alfiany (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
To become the halal centre of the world, the government requires the implementation of halal certification for all products circulating in Indonesia, one of which is food and beverage products. The halal certification obligation has been carried out from 17 October 2019 to October 2024. The government has prepared strategies to improve the quality and quantity of assistants and simplify the halal certificate registration process. The Sukabumi City Diskumindag has helped facilitate MSMEs in Sukabumi City to register for free halal certification. However, there are still many MSMEs in Sukabumi City that do not have halal certificates. This is certainly detrimental to the community because it does not protect the right to safety and comfort when consuming or using a product. If until 18 October 2024 MSMEs are not halal certified, they will be subject to sanctions in accordance with Article 24 of the Law on Halal. This study aims to examine how the implementation of halal certification is viewed from Law Number 33 of 2014 concerning Halal Product Guarantee for MSME players in Sukabumi City as well as the role of Diskumindag Sukabumi City and what obstacles are faced during the implementation of the Law. The research used in this study is normative juridical which deductively reviews articles and legislation to examine how these regulations are applied in practice. Problems in the implementation of Law Number 33 of 2014 concerning Halal Product Guarantee in Sukabumi.